2019
DOI: 10.1016/j.hlc.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography: Navigating Complexities to Provide Many Useful Applications in Contemporary Clinical Cardiology

Abstract: Echocardiography has been around for more than half a century [1]. Recent decades have seen significant technological advances, with increasing clinical applications of this non-invasive imaging tool, beyond the basic assessment of left ventricular function, with further evolution evident on the horizon. There has also been a burgeoning increase in use: According to the 2017 Australian Medicare Medical Benefits Schedule (MBS) Taskforce, about 900,000 echocardiographic procedures (excluding stress echo) are rei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…8 Through three-dimensional volume measurement, the heart shape and structure can be truly stereoscopic, with good repeatability and high accuracy. 9 The Echocardiography of the present study revealed a fatty mass structure on the valves in the rheumatic mitral valve. In addition, we found that the damaged valve turned into fatty yellow adipose tissue under the naked eye, which also suggested that the damaged valve lesions were associated with adipose tissue changes, which suggested that adipokines were involved.…”
Section: Immunohistochemical Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…8 Through three-dimensional volume measurement, the heart shape and structure can be truly stereoscopic, with good repeatability and high accuracy. 9 The Echocardiography of the present study revealed a fatty mass structure on the valves in the rheumatic mitral valve. In addition, we found that the damaged valve turned into fatty yellow adipose tissue under the naked eye, which also suggested that the damaged valve lesions were associated with adipose tissue changes, which suggested that adipokines were involved.…”
Section: Immunohistochemical Resultssupporting
confidence: 51%
“…Echocardiography is recommended by the World Heart Federation for the screening and diagnosis of RHD 8 . Through three‐dimensional volume measurement, the heart shape and structure can be truly stereoscopic, with good repeatability and high accuracy 9 . The Echocardiography of the present study revealed a fatty mass structure on the valves in the rheumatic mitral valve.…”
Section: Discussionmentioning
confidence: 47%
“…The addition of POCUS to the standard clinical assessment has the potential to influence all facets of health care, from the immediate medical decisionmaking process to the health care system more broadly. This effect is probably greater in resource-limited locations where access to comprehensive studies can be restricted (Gregory et al 2019).…”
Section: Introductionmentioning
confidence: 99%